Systematic Studies in Herbaceous Phyllanthus Spp. (Region: Tiruchirappalli District in India) and a Simple Key to Authenticate 'Bhumyamalaki' Complex Members - Vinithra2 and S. Sekar1*, D. Kandavel1, S. K. Rani2 and M. G. (Journal of Phytology, 2011)
The taxonomic status of Phyllanthaceae and current systematic position is highlighted. In India, 12 herbaceous species of Phyllanthus have been identified and among them herbs referred to as ‘Bhumyamalaki' complex has been extensively used as traditional medicine for various ailments. The medicinally important herb in this group is P. amarus Schum. & Thonn. and is often adulterated with its allied species and hence a simple key to differentiate them is evolved as confusion exists in identification of these herbaceous species due to their similarity and close proximity. P. niruri L. is a native of New World and endemic to America and does not occur in India, although there are many publications in India claiming work on P. niruri L. Those reports are actually pertaining to investigations in ‘niruri complex’ but not on P. niruri L. Herbaceous Phyllanthus species found in Tiruchirappalli district has been recorded and their morphological and anatomical parameters were assessed and a simple key developed. SCAR Analysis for validating the identity of P. amarus is presented for authentication at molecular level. P. debilis, a coastal zone species is first reported from an inland area. Key words: Phyllanthus amarus, Phyllanthus debilis, Phyllanthus maderaspatensis, Phyllanthus virgatus, Phyllanthus fraternus, Phyllanthus urinaria, Phyllanthaceae, Morphology, Taxonomic key, Herbal Authentication <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-fareast-language: EN-SG; mso-font-kerning: 0pt; mso-no-proof: no; mso-ansi-language: EN-SG;" lang="EN-SG">Dhandayuthapani Kandavel et al. Systematic Studies in Herbaceous Phyllanthus Spp. (Region: Tiruchirappalli District in India) and a Simple Key to Authenticate 'Bhumyamalaki' Complex Members. J Phytol 3/2 (2011) 37-48.